2006
DOI: 10.1002/net.20116
|View full text |Cite
|
Sign up to set email alerts
|

The one‐commodity pickup and delivery travelling salesman problem on a path or a tree

Abstract: Optimization algorithms for both path and tree topology classes of the one-commodity pickup and delivery travelling salesman problem (1-PDTSP) are proposed in this article, which focus on minimizing the route distance to transport products among pickup and delivery customers by a single vehicle with a limited capacity of k . Each pickup customer provides one unit volume of the product while each delivery customer requires one unit volume of the product. For the path case, we propose an O(n 2 / min (k , n)) alg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 12 publications
0
19
1
Order By: Relevance
“…Note that since we require that the vehicle leave and return to the depot without any bike, our problem is different to the problem considered in previous study (Hernandez-Perez and Salazar-Gonzalez 2002, 2004a, 2007Hernandez-Perez et al 2009;Louveaux and Salazar-Gonzalez 2008;Wang et al 2006;Zhao et al 2009), therefore our numerical results are not comparable to the results provided therein.…”
Section: Computational Experimentscontrasting
confidence: 58%
See 2 more Smart Citations
“…Note that since we require that the vehicle leave and return to the depot without any bike, our problem is different to the problem considered in previous study (Hernandez-Perez and Salazar-Gonzalez 2002, 2004a, 2007Hernandez-Perez et al 2009;Louveaux and Salazar-Gonzalez 2008;Wang et al 2006;Zhao et al 2009), therefore our numerical results are not comparable to the results provided therein.…”
Section: Computational Experimentscontrasting
confidence: 58%
“…The goal is to minimize the total cost of the trip. The depot serves as a "buffer", i.e., the vehicle is allowed to leave the depot with an amount of load and/or to return to the depot with an amount of remains, see Hernandez-Perez and Salazar-Gonzalez (2002, 2004a, 2007, Hernandez-Perez et al (2009), Louveaux andSalazar-Gonzalez (2008), Wang et al (2006) and Zhao et al (2009). There have been several studies focusing on this problem since it was proposed.…”
Section: Literature Reviewmentioning
confidence: 97%
See 1 more Smart Citation
“…The Q-DTSP on a line and on a tree has been studied by Wang et al (2006). For the line case, the authors have presented an O(n 2 /min{Q, n}) algorithm and have shown how to solve the unit capacity version (Q = 1) and the uncapacitated version (Q = ∞) in linear time.…”
Section: The Q-delivery Traveling Salesman Problem [M-m|p/d|1]mentioning
confidence: 99%
“…They have also presented a heuristic with a worst-case performance ratio of 1.5, and they have shown that in the single commodity case the problem can be solved in polynomial time. A linear time algorithm for the single-commodity, a non-preemptive version of the SP on a tree, is presented by Wang et al (2006) is a many-to-many, single-commodity problem. The set of customer locations is partitioned into pickup and delivery customers to be served by a single vehicle based at the depot.…”
Section: The Swapping Problem [M-m|p-d|1]mentioning
confidence: 99%